Aussie footy--adapting sport to meet the needs of young children - Douge, Brian (National Football League, 1987)
Well meaning administrators and coaches in junior sport too often neglect the real needs of kids. Substantial evidence is available to show that sporting environments which emphasise competition played under adult rules, are inappropriate for young children. As a consequence, there is a need to adapt the game so it caters for the physiological and psychological capabilities of young children.